Transformasi Praktik Akuntansi dan Laporan Berkelanjutan Melalui Asuransi Karbon - Anjani, Angelica Dara Wahyu; Hanjaya, Anthony Evan; Gwendella, Richelly; Nelson, Catheryn Iona; Breliastiti, Ririn (Journal of Business And Entrepreneurship, 2025)
The study presented in this paper examines how carbon accounting can be implemented as a part of a company sustainable strategy, bringing changes to accounting practices to address global challenges such as climate change. Carbon accounting is crucial for measuring and reporting the greenhouse gas (GHG) emissions emitted by either human or business activites. This reasearch uses a quantitative descriptive method with secondary data obtained from Sustainablity Reports in 2023 of companies listed on Indonesia Stock Exchange. Our findings show that companies apply various methods to calculate their GHG emissions. These methods include the Greenhouse Gas Protocol guidelines, the Global Reporting Initiative (GRI), and other international standards. They cover the measurement of Scope 1, 2, and 3 emissions as well as the deployment of low-carbon technologies in the transition to renewable energy. Our study also recommends that companies enhance the transparency and efficiency of their sustainability reporting by strengthening their carbon accounting frameworks.